Penegakan Hukum Pidana Terhadap Kakek Pelaku Pelecehan Bagi Anak Di Dalam Kapal - Lesnussa, Agnes G; Latupeirissa, Julianus Edwin; Salamor, Anna Maria (PATTIMURA Law Study Review, 2025)
Sexual harassment is sexual activity that occurs verbally, non-verbally and also visually, namely sexual behavior that is unwanted by the victim, targeting the victim’s sexual organs or sexuality. Women and children often become victims of sexual harassment. The rise in cases of sexual abuse against children is one form of lack of handling by law enforcement officials in safeguarding, preventing and protecting children from criminal acts of sexual abuse. Parents, the community and law enforcement officials are expected to provide guarantees of legal protection for children who are victims of criminal acts of sexual abuse. The research method used in researching and discussing this problem is normative juridical which uses a statutory approach, a conceptual approach and a case approach. The legal materials used are primary, secondary and tertiary legal materials. Sexual harassment is sexual activity that occurs verbally, non-verbally and also visually, namely sexual behavior that is unwanted by the victim, targeting the victim’s sexual organs or sexuality. Women and children often become victims of sexual harassment. The rise in cases of sexual abuse against children is one form of lack of handling by law enforcement officials in safeguarding, preventing and protecting children from criminal acts of sexual abuse. Parents, the community and law enforcement officials are expected to provide guarantees of legal protection for children who are victims of criminal acts of sexual abuse.